THE DIGITALIZATION OF THE INFORMATION SYSTEM TO IMPROVE PERFORMANCE USING THE WARD AND PEPPARD APPROACH AT PT. ANANTA AUTO ANDALAN - Damayanti, Murni; Waspodo, Bayu (JURNAL PERANGKAT LUNAK, 2024)
In an increasingly competitive business environment, the digitalization of information systems has become crucial for manufacturing companies to enhance operational performance and competitiveness. This research examines the implementation of the Ward and Peppard approach in the digitalization of information systems at PT Ananta Auto Andalan. The background of this research is the need for PT Ananta Auto Andalan to optimize the effectiveness and efficiency of information systems in supporting business operations. The research methodology involves in-depth analysis of the existing organizational structure, job descriptions of each work unit, and internal and external environmental analysis of the company. By utilizing the Ward and Peppard approach, this research yields detailed strategic recommendations, including upgrading internet bandwidth from 10 Mbps to 20 Mbps to meet the company's computer network needs. Mapping information requirements for each division also becomes a primary focus in the development of information system digitalization strategies. The research findings indicate that adopting the Ward and Peppard approach provides a comprehensive framework for PT Ananta Auto Andalan to address dynamic changes in the business environment. The strategic recommendations generated include proposals for an IT/IS organizational structure tailored to the company's needs and business demands. The conclusion of this research asserts that the implementation of the Ward and Peppard approach can assist companies in effectively leveraging information systems to achieve their business goals. It provides clear insights and directed solutions to challenges in the digital era